MENINGKATKAN AKTIVITAS DAN KEMAMPUAN HOT (HIGHER ORDER THINKING) SISWA SDN BANYU LANDAS KABUPATEN BARITO TIMUR PADA MATERI GEOMETRI MENGGUNAKAN MODEL PROBLEM SOLVING - Uyani, Silvia (Vidya Karya Jurnal Kependidikan, 2014)
This research relates to the impeimentation of Problem Solving model in Elementary School Banyu Landas. The research objective is to increase the studentsâ learning activity and teacherâ activity quality as well as to increase the studentsâ HOT (Higher Order Thingking) skills on geometry. The research is based on the classroom action research (CAR) through 2 cycles. The subject is 10 students of six class in SDN Banyu Landas. The data collection used studentsâ and the teacherâs activity obeservation sheets as well as achievment result. The data were qualitatively analyzed with percentage technique. The result of research stated that (1) the quality of teacherâs activity increasedÂ from 58,41% in the first cycle Â up to 71,14% in the end of second cycle; (2) studentsâ activity incresedÂ from 68,39% in the first cycleÂ up to 70,10% in the end of second cycle; and (3) the studentâ HOT (Higher Order Thingking) skills increased from analysis skills 77,85% in the first cycle upto Â synthesys skills 86,58% in the end of second cycle.